Objects as Participants in the Democratic Assemblage: A Playful Exploration of the Affective Materiality of Junk - Asenbaum, Hans; Poulsen, Mathias (Theoria (Pietermaritzburg), 2025)
Objects, their material affordances, and agentic potentials are neglected by research on democratic participation. This article draws on new materialist assemblage theory to make sense of objects in participatory settings and explores the claim that objects may act as participants. It conceptualises participatory processes, commonly framed as democratic innovations, as democratic assemblages, which draws attention to the affective role of nonhumans, including material objects. These assemblages function as a democratic microverse that prefigures democratic futures. To deepen and substantiate these theoretical claims, the article infuses new materialist thinking with ethnographic observations from junk playgrounds, in which human participants interact with discarded materials in response to a political question. We observe how objects resist, invite, and transform humans and make the case for more playful and joyful democratic engagements.